Automation experiments in physics laboratories - Perea Martins, J. E.M. [UNESP] (IOP Publishing, 2018)
This work presents experiments to teach fundamentals of automation through a sequence of laboratory practices that naturally guide to development of an on/off control system. It focuses on the integration of technological and scientific concepts, based on an educational approach associated with a problem-solving technique.